Educação linguística: caminhos para o ensino da língua materna - SOUZA, Ana Kennya Félix Ribeiro de (2012)
Address in this paper the conceptions of teaching of mother tongue and the theoretical assumptions that explain the emergence of belief in the homogeneity of Portuguese language and prejudice rooted in the educational practices of language teaching. Therefore, rescues briefly the socio-history of Brazilian Portuguese bounding up the objectives of the teaching of Portuguese in school, in the light of official documents (PCN and Curricular Guidelines), criticizing certain practices embedded in the school culture. Emphasis is placed on the Education Linguistics aimed to broaden the students' communicative competence and presents a brief analysis of the texts of high school students at the Federal Institute of Maranhão, to give visibility to the conceptions of language that are still rooted in the culture of students, using some elements of discourse theory.